PENANGGULANGAN KEKERASAN TERHADAPANAK (Child Abuse) DALAM KELUARGA (Perspektif Pendidikan Agama Islam) - Salis Irvan Fuadi (Manarul Qur'an: Jurnal Ilmiah Studi Islam, 2018)
The concept of violence against children includes several things:Definition of violence against children (child abuse), other forms ofviolence against children (child abuse), elements of violence againstchildren (child abuse). Islamic education is an alternative educationto guide while also directing students toward the establishment of aprivate key (perfect man) based on the ethical values of Islam whilemaintaining good relations against Allah neighbor, herself and thesurrounding nature .. As for the prevention of violence against childeducational perspective of Islam, which must be implemented byparents, namely: provide exemplary child, think before runningthings, binds hearts before explaining, introduced before the burden,hang the child, not dictate, rectifying the error is not stripped,reward, punish wisely, sanctions educate, to avoid punishment thatdoes not educate, do not bring up a previous state, and warmthafter the punishment.